Polarization Effect Assessment of Sub-6 GHz Frequencies on Adult and Child Four-Layered Head Models - Pudipeddi, S. S.; Jayasree, P. V. Y.; Chintala, S. G. (Engineering, Technology & Applied Science Research, 2022)
Nowadays, with the extensive use of mobile phones, the Electromagnetic (EM) radiation penetration from Radio Frequencies (RFs), particularly into the human head, is an issue that needs resolving. Some serious biological hazards occur inside the human body due to RF radiation accumulation. The RF radiation can be minimized by embodying shielding and coating materials on the front side of the mobile handset. The novelty of the proposed work is the use of mathematical analysis in calculating the Specific Absorption Rate (SAR) absorbed by planar four-layer adult and child head models when exposed to mobile smartphone RF radiation. The variation of SAR with the Angle of Incident (AoI) of the EM wave considers Transverse Electric (TE) and Transverse Magnetic (TM) Polarization. The SAR absorption alteration with the AoI of the EM wave is calculated with the help of the shielding effectiveness parameter of the external Polyethylene Terephthalate (PET) shield coated with conductive copper (Cu) mesh, forming a laminated shield using the methodology of the transmission line method. Furthermore, the SAR variation with AoI for both human head models is calculated theoretically at Sub-6 GHz mobile frequencies of 4.5GHz and 3.6GHz. SAR of 7.41e-12 W/kg and 4.41e-11 W/kg is achieved theoretically for adult and child head models respectively, at 89° TE polarization at 4.5GHz.